Voices of the Disenfranchised Within the Academy: Black Faculty Matter - Ruby Cain (Adult Education Research Conference, 2016)
This Roundtable Session will provide an overview of the research literature on the challenges of Black faculty’s journey to promotion and tenure. The participants will be engaged in an interactive discussion of this topic
Keywords: Black faculty; promotion and tenure